Trends in reporting on climate change, water and COVID-19 by JSE listed companies - Seedat, Zakiyyah (University of the Witwatersrand, Johannesburg, 2022)
Environmental, social and governance (ESG) information is increasingly demanded by stakeholders as companies face risks and opportunities due to ESG issues, such as climate change, water and COVID-19. ESG disclosure helps reduce information asymmetry for users of company reports and helps companies maintain their social licence to operate. Disclosure is voluntary and this introduces differences in the information disclosed by companies. This study analysed the annual, integrated and ESG reports of the top 40 Johannesburg Securities Exchange (JSE) listed companies. These reports were analysed following an interpretive approach to determine the extent of disclosure on climate change, water and COVID-19 in 2018, 2019 and 2020. This study also considered the change in disclosure on climate change and water over these three years. A disclosure checklist has been developed using professional literature. Content analysis has been used to codify the disclosed information with disclosures being scored using an ordinal scale. Descriptive statistics have been used to analyse and graphically present the data. Exploratory factor analysis has been used for the identification of major disclosure themes. This study contributes to existing research by considering the current state of ESG disclosure at a time when notable developments in the reporting environment have occurred. The findings indicate that companies have focused on quantitative and strategy-related disclosure, indicating the adoption of similar reporting practices by companies. The study also found that there was no significant change in climate change and water disclosure from 2018 to 2020
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Commerce in Accountancy, University of the Witwatersrand, Johannesburg, 2022
Keywords: ESG reporting; Sustainability reporting; Climate change; Water; COVID-19; South Africa; UCTD; SDG-6: Clean water and sanitation; SDG-13: Climate action; SDG-3: Good health and well-being